Analisis Jenis dan Karakteristik Limbah B3 dari Industri Smelter Nikel di PT.X - Sah Ahmada Fibra; Eka Wardhani (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This research is to analyse the types of characteristics Toxic and Hazardous Waste (THW) from the nickel smelting industry at X Company. The research method uses descriptive analysis by identifying the production process and also identifying the types and characteristics of THW at company generated based on the cause, namely THW category 1 and category 2. Meanwhile, the characteristics of THW that company main and supporting facilities, where these supporting facilities include the nickel smelter production process from start to packaging, and also these supporting facilities include a diesel fuel station, generator room, electric power source, clean water supply station, workshop, warehouse, air compressor, storage (stockpile) for products, temporary slag, office building, dining room, laboratory, nitrogen station, liquid oxygen station and oxygen filling room. The types of THW produced are based on categories, namely Category 1 and Category 2 THW. The characteristics of the THW that X Company produces a lot of are THW with toxic characteristics and a small part of THW with characteristics of flammable liquids and flammable solids.